Investigation on Student Perspective Toward the Use of Music in English Learning Process - Rahman, St. Aulia; Talib, Ahmad; Fauzan, Muhammad Miftah (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2025)
This study investigates students' perspectives and the impacts of using music in the English learning process. Conducted with 35 students from the English Education Study Program at Universitas Negeri Makassar, the research employed a sequential explanatory mixed-methods design, combining quantitative data from Likert-scale questionnaires and qualitative insights from interviews. The quantitative analysis revealed a mean score of 100.31, indicating an overall positive perspective among students. Key findings demonstrated that music enhances motivation (77.15% agreement), improves vocabulary retention (74.29%), and creates a relaxed learning environment (62.86%). Students also reported increased confidence and engagement. However, challenges such as fast-paced lyrics (60% agreement) and occasional pronunciation difficulties were noted. Qualitative interviews corroborated these results, highlighting music’s role in reducing anxiety and fostering enjoyment. The study concludes that integrating music into English learning is highly beneficial, supporting cognitive and emotional aspects of language acquisition. Recommendations include incorporating diverse music genres, addressing pronunciation challenges, and optimizing song selection to align with learners’ proficiency levels. These findings underscore music’s potential as an effective pedagogical tool, encouraging educators to leverage its advantages while mitigating identified challenges.